Comparison of Active Summer and Winter Sports Tourists in a German Highland (Laisvalaikio tyrimai, 2018)
Research background. During the last decades the importance of sports tourism has risen (e.g. Schwark, 2007). A lot of new destinations have developed and existing destinations have expanded. Gaining information about sports tourists is important for destinations because of the increased competition in that field. On the other hand, the phenomenon of sports tourism has also become the focus of scientific work. Understanding consumers is one major field within this topic (Konu, Laukkanen, Kommpula, 2011). The destination choice process is of particular interest. According to the model of P. Pearce (2005, p. 109) adapted by H. Konu et al. (2011, p. 1098), which is used in this research, internal as well as external factors influence the destination choice process in sports tourism. Sports tourism plays an important role in German highland destinations (Aderhold, 2011). Traditionally, these destinations concentrate on winter sports tourism. As a consequence of climate and demographic changes, creating all-year marketing strategies is important. At the same time, there is a lack of knowledge regarding studies dealing with the comparison of sports tourists of different seasons. Research aim. This study deals with internal factors influencing destination choice and tourism behaviour of active sports tourists. The main objective of this research was to investigate whether there were differences between active sports tourists in summer and winter or not. Therefore, active summer and winter sports tourists of one German highland destination (Ore Mountains) were compared. Methods. Data were collected using a standardized questionnaire during one winter and one summer season. Differences between active summer and winter sports tourists regarding socio-demographic variables were examined firstly. Afterwards a factor analysis (PCA with varimax rotation) was used to reduce internal factors (motives) in order to investigate whether there were differences regarding the destination choice process. Finally, travel behaviour of active sports tourists was analysed. Significance of differences was statistically proved by analysis of contingency, t-test or Welch-test. Results and conclusions. Active summer and winter sports tourists of the Ore Mountains do not differ regarding age and gender. Out of 15 motives influencing the destination choice process six factors could be extracted. Summer and winter sports tourists differ only in two of them from each other. There are differences regarding the length of stay, travelled distance to destination and expenditure within the destination. Active sports tourists in winter stay longer, travel a longer distance to reach the Ore Mountains and spend more money there. As a conclusion, developing all-year marketing strategies for active sports tourists of one destination seems to be helpful, as tourists of different seasons are comparable. Of course, this study can provide only initial information about the comparison of active sports tourists of different seasons. In order to generalize the findings, further research should be done.Keywords: sports tourism, highlands, active sports tourists, destination choice process.